(3TQM Yjf GdYde hRjf GdMdes - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd NGOe cdGe QHg GdbOje hMOjK QShdg GdaNje Ydj Hf SdWGf eMeO GdbGQi s
(3BNQgG (B:s
(3CfhGY GdScjfI MGeOkG heUdjkG hGdUdGI hGdSdGe Ydi SjO GdeQSdjf hCaVd GdNdb CLeYjf hYdi Bdg hCUMGHg hCJHGYg Edi jhe GdOjf Bejf Bejf HMQeI SjO GdeQSdjf s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJUha hGdBOGH GdTQYjIs